Socioeconomic and Educational Stratification in Private Colleges in China - Hao, Li (Technium Education and Humanities, 2021)
Higher education has always been positioned as a key factor in achieving social mobility and equality in Chinese culture. The assumption that more higher education opportunities from private colleges could help to increase social equality became entrenched in society during the last decades. Basing the analysis upon recent empirical studies conducted in private colleges in China, I review the current situation of educational and socioeconomic stratification in students and teachers respectively. Realising that students and teachers of different socioeconomic origins may have diverse experiences and opportunities in private colleges and labour markets, this study critically reflects upon how variations in economic capital and social capital have impacted on a person’s career development and social mobility as private higher education has massively expanded in China. This study finds that in contemporary China, socioeconomic stratification is a more important and influential factor than educational stratification. It also reveals a strong and increasing cumulative effect of family socioeconomic status throughout a person’s educational and professional career, which is mainly caused by their socioeconomic strata, instead of educational strata at each transition. This study then concludes that socioeconomic stratification and the crowding-out effect, rather than social mobility and equality, are the likely results of private higher education expansion in China. This study is original and meaningful because it is based on first-hand evidences collected through the researcher’s more than ten years of practice and exploration in several private colleges in China.